Prevalence and factors interfering in regained weight in women who underwent Gastric Bypass Roux-Y, 2 years after bariatric surgery - da Silva, Renata Florentino (2014)
Aim: To analyze the prevalence and the interfering factors of the regain weight in women who underwent to the gastric Bypass in Y of Roux two year after bariatric surgery. Materials and Methods: Was conducted an analytical research; transversal; descriptive. The sample consisted of 30 patients during the period from December 2012 to August 2013. A questionnaire was applied in which were evaluated: the weight, physical activity, and the average time to realize of the main meals, difficulty chewing and the use of protein supplementation. Results:The regain weight among persons who practice physical activity (3,34 ± 2,23) was lower than in persons who do not practice (9,2 ± 10,3). The persons who do not practice physical activity earn an average 1,5 kg more than those who practice. As observed there is a the greater trend regain weight, patients who consume less protein and have the habit of snacking. Conclusion:The surgery does not end the treatment of obesity, and the ancillary therapies have to be associated to the continuous monitoring of the multidisciplinary team. However more research is needed in order to elucidate the predictors’ factors of regain weight.